2017
DOI: 10.1088/1361-648x/aa75c1
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling electron- and electric-field-induced ring-closing reactions in a diarylethene derivative on Ag(1 1 1)

Abstract: Using scanning tunneling microscopy and spectroscopy we investigate the adsorption properties and ring-closing reaction of a diarylethene derivative (C5F-4Py) on a Ag(1 1 1) surface. We identify an electron-induced reaction mechanism, with a quantum yield varying from 10-10 per electron upon variation of the bias voltage from 1-2 V. We ascribe the drastic increase in switching efficiency to a resonant enhancement upon tunneling through molecular orbitals. Additionally, we resolve the ring-closing reaction even… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…7. From this plot R ' I N , N = 0.68 was determined, which corresponds to the molecular switching behavior reported by Reecht et al (2017). A power N = 1 would suggest a one-electron process.…”
Section: Figuresupporting
confidence: 67%
See 2 more Smart Citations
“…7. From this plot R ' I N , N = 0.68 was determined, which corresponds to the molecular switching behavior reported by Reecht et al (2017). A power N = 1 would suggest a one-electron process.…”
Section: Figuresupporting
confidence: 67%
“…It is well known that energy can be transferred from a tunneling electron to a molecule adsorbed on a surface and induce, for example, vibrational and/or rotational excitations (Reecht et al, 2017). Since rotation implies some type of partial transfer of angular momentum, rotational excitation is more complex than vibrational excitation.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…(Figure g‐h) and also performed conductance switching experiments and imaged dI/dV maps . In a subsequent report on the same compound, the authors showed that the switching could be induced either by tunneling electrons or the electric field between the tip and surface …”
Section: Stm Of Diarylethenesmentioning
confidence: 89%
“…[86] In a subsequent report on the same compound, the authors showed that the switching could be induced either by tunneling electrons or the electric field between the tip and surface. [87]…”
Section: Diarylethenes Under Uhvmentioning
confidence: 99%